Litewskie siedziby Zanów – Dukszty, Gierkany, Hryszkowszczyzna i Poniemuń. Postscriptum wspomnień Tomasza Zana i Heleny z Zanów Stankiewiczowej - Brodzka-Bestry, Maria (Komunizm: System - Ludzie - Dokumentacja, 2023)
This article was written on the occasion of the conference ‘The extermination of the Polish gentry in the former eastern territories of the Republic of Poland in 1939- 1945’. It is the first attempt to recreate the history of the four eastern settlements of the Zanfamily of landowners, and the architecture and interiors of their possessions, based on the published memoirs of Tomasz Zan and his sister, Helena Stankiewicz née Zan, the great-grandchildren of the member of ‘Promieniści’ circle Tomasz Zan, a friend of Adam Mickiewicz. The publication also uses previously unpublished photographs and plans from the family collection. At the turn of the 18th and 19th centuries, many mansions in Classical style were built in the Grand Duchy of Lithuania, some of them similar to Dukszty (Dūkšteliai), a one-story manor house with a two-story central part and a portico in giant order. The manor house in Dukszty was built in the first quarter of the 19th century, and could have been designed by an architect from the circle of Wawrzyniec Gucewicz. Gierkany (Gerkonys) is a small wooden, plastered, one-story mansion on a rectangular plan, built at the end of the 19th century, resembling the larger manor house in Hryszkowszczyzna (Griškiškė), which probably dates back to the 18th century. In Poniemuń (Žemoji Panemunė), next to the ruins of the palace, the Gothic cellars of the former castle have survived. After World War II the Zan familylost their property, which then found itself in the Soviet Union. The manors in Dukszty and Gierkany were devastated and stripped of their furnishings,but survived. The wooden manor house in Hryszkowszyzna was burned down, as was the chapel. The manor house in Poniemuń, which was lost in 1923, remained, however as ruin, and the entire property was returned to the pre-war Lithuanian owner.